Six important theories in information behaviour research: a systematic review and future directions - Yang, Xinyue; Yuan, Qinjian (Information Research an international electronic journal, 2022)
Introduction. The fragmentation and appropriation of fundamental theories from other disciplines have increasingly hindered the carrying-out of empirical studies in information behavioural research. Six theories were selected, with ethnographic decision tree theory and means-end chain theory exploring how behaviour happens and will evolve, media richness theory, collective action theory and service encounter theory exploring why behaviour happens and motivation crowding theory exploring why things go off track. Method. Topic-relevant empirical studies of the applications of six theories published in Web of Science Core Collection have been collected and reviewed. Analysis. Theory development, research agenda and current problems, as well as potential directions for future research were illustrated. Results. Our findings indicated that the six theories have broad application contexts and their application potential needs to be further explored. Conclusions. This paper has important implications for advancing the boundary conditions regarding these theories and relevant empirical studies, as well as discovering uncharted territories.